Dyskryminacyjne metody klasyfikacji danych w prognozowaniu bankructwa firmy - Pociecha, Józef (Discriminant methods of data classification for bankrupcy prediction, 2006)
Discriminant analysis consists of assigning an individual to two or more distinct populations, on the basis of observations on several characters of the individuals and a sample of observations on these characters from the populations. R. A. Fisher suggested a linear function, called linear discriminant function, for classifying an individual into one of two populations. E. I. Altman adapted this approach to identify bankruptcy risk of corporations. Altman’s model of bankruptcy was estimated for various countries, thereby for Polish economy. Some results of estimation and interpretation of Altman model are presented in the paper. Methodological and application problems of bankruptcy prediction are also discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 83-92